IFN-β and ARTS deficiency promote the generation of hyper-efferocytic Ly6C+ macrophages in resolving inflammation in male mice - Orly Zeituni-Timor; Soaad Soboh; Ahmad Zaid; Hiba Yaseen; Senthil Kumaran Satyanarayanan; Maha Abu Zeid; Esther Silberberg; Priya Goswami; Sagie Schif-Zuck; Sarit Larisch; Amiram Ariel (Communications Biology)
Abstract During the resolution of inflammation, Ly6C+F4/80- monocytes differentiate to Ly6C-F4/80+ macrophages that exert apoptotic cell engulfment (efferocytosis) properties and consequently convert to interferon (IFN)-β-producing macrophages. Here, we report that exposure to IFN-β, or transforming growth factor (TGF)-β, or a deficiency in the pro-apoptotic protein ARTS, results in the conversion of mature macrophages to an Ly6C+F4/80+CCR2+ phenotype in vivo and ex vivo. Deficiency in ARTS or caspase inhibition results in enhanced conversion of macrophages to the Ly6C+ phenotype. Moreover, IFN-β-triggered Ly6C+ macrophages are hyper-efferocytic and express higher levels of the efferocytic receptor CD36. Inhibition of CD36 ligation results in complete abrogation of efferocytosis ex vivo in both Ly6C+ and Ly6C- macrophages. Notably, IFN-β also promotes the emergence of Ly6C+ macrophages during the resolution of liver fibrosis, while transcriptomic analysis further links this rejuvenated phenotype to macrophage subsets found in human inflammatory liver disease. Altogether, our findings indicate IFN-β promotes macrophage conversion to a distinct hyper-efferocytic phenotype that is limited by ARTS and apoptosis during the resolution of inflammation.